Kajian Potensi dan Strategi Pengembangan Agrowisata Taman Gading Asri Jember - Prabowo, Rachmat Udhi; Ardhana, Aditya Yoga; Yulianti, Annisa; Alizza, Tsaniya Nibraas; Alfaroh, Vika Anjana (Program Studi Agribisnis, 2023)
Taman Gading Asri Agrotourism is a horticultural agricultural object packaged with a tourism concept located in Jember Regency, but currently it has not been developed optimally. Study carried out aimed at managers of horticultural plant cultivation at Taman Gading Asri Agrotourism. Research design used is qualitative with case study research techniques. Analysis plan The data used is qualitative descriptive analysis and SWOT analysis. From the results of the research that has been carried out it is known that Taman Gading Asri agrotourism activities start from education regarding the production process of horticultural crops by applying welfare rules for tourist attractions to culinary tourism. The strategy that has been implemented by Taman Gading Asri Agrotourism in Agrotourism development is making plans to improve facilities on location, improving customer service, and carrying out promotion of agrotourism through social media. The most appropriate strategy and The priority in developing Taman Gading Asri agrotourism is an aggressive strategy with increasing the various agrotourism attractions of Taman Gading Asri and expanding marketing.